Tailor-made starch-based conjugates containing well-defined poly(vinyl acetate) and its derivative poly(vinyl alcohol) (eXPRESS Polymer Letters, 2011)
Reversible addition-fragmentation chain transfer (RAFT) polymerization was adopted to synthesize starch-based conjugates that possessed controllable architecture and properties. Starch-based xanthate agent was prepared and applied as chain transfer agent to conduct the living/controlled polymerization (LCP) of vinyl acetate, which generated tailor-made conjugates of starch and well-defined poly(vinyl acetate) (SVAc). The relevant derivatives, conjugates of starch and chain length-controlled poly(vinyl alcohol) (SVA), were obtained subsequently. Various characterizations such as Fourier transform infrared spectra (FTIR), ultraviolet-visible spectroscopy (UV), proton nuclear magnetic resonance (1H NMR), gel permeation chromatography (GPC), X-ray diffraction (XRD), Thermogravimetric analysis (TGA), and dynamic mechanical thermal analysis (DMTA) were performed to examine the structure of intermediates and the starch-based conjugates. Static contact angle measurements revealed that the hydrophilic character of starch-based conjugates was tunable. Well-defined SVAc was amphiphilic and it was able to self-assemble into size controllable micelles, which was verified by contact angles, transmission electron microscopy (TEM) and dynamic light scattering (DLS) tests. SVA exhibited much higher capability to form physically cross-linked hydrogel than starch did. Both the characteristic of SVAc and SVA were chain length-dependent.